ANALISIS PERBANDINGAN KINERJA SAHAM SYARIAH SEBELUM DAN SESUDAH PENGUMUMAN KENAIKAN BBM - ANITA ANITA (Universitas Islam Negeri Imam Bonjol Padang, 2016)
This study aims to look at the differences of Islamic stocks on the Indonesia Stock Exchange (BEI) before and after the announcement of the price increase of fuel oil (BBM) on 15 May 2015. The method used is quantitative research with paired sample t-test. Research shows that there are significant differences abnormal return before and after the announcement of fuel price increases as well as demonstrate the difference by delaying the trading activity in the stock transaction that makes the average transaction decreased from prior events (event).